Comparative evaluation of remaining dentin thickness with three different rotary Ni-Ti File systems: an in vitro CBCT study - Durga Bhavani, P; Sita Rama Kumar, M; Sajjan, Girija S; Madhu Varma, K; Kalyan Satish, R; Manishaa, B (International Journal of Dental Materials, 2022)
Background: Endodontic therapy and its success depend on effective cleaning and shaping the root canal without deviating from the original anatomy. Ideally, during root canal preparation, the instruments should always confine to and retain the original shape of the canal to maximize the cleaning effectiveness and minimize unnecessary weakening of tooth structure to achieve the optimal result. The remaining dentin thickness in endodontically treated teeth is a significant factor, which is responsible for its longevity.Aim: This study aimed to evaluate the remaining dentin thickness after instrumentation with ProTaper Next (PTN), TruNatomy (TN), and Neohybrid (NH) file systems using cone-beam computed tomography.Materials and methods: Thirty extracted single-rooted mandibular premolars were decoronated and divided into three experimental groups with ten in each. Groups I, II, and III were assigned to the file systems ProTaper Next (PTN), TruNatomy (TN), and Neohybrid (NH), respectively. Cone-beam computed tomographic pre-scans were taken, followed by the biomechanical preparation with the respective file systems. Post CBCT scans were taken and compared with pre-scans for remaining dentin thickness. The data obtained were statistically analyzed.Results: Among the three file systems, TruNatomy rotary files resulted in significantly less dentin removal (p